2019
DOI: 10.17398/2340-4256.14.475
|View full text |Cite
|
Sign up to set email alerts
|

Aportaciones de la gerotrascedencia en el envejecimiento: una visión centrada en la ética de necesidades

Abstract: En este artículo se desarrolla una formulación operativa de la teoría de la gerotranscendencia de Tornstam (1989, 2000, 2011) para justificar las intervenciones en el adulto mayor centradas en la ética de necesidades, a diferencia de la óptica tradicional basada en los cuidados. Partiendo de una justificación sobre la vulnerabilidad de esta etapa del ciclo vital en claves emocionales y de soledad, se delimita la cuestión del sentido vital como elemento fundamental de la teoría. A continuación, se desarrolla un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…In another study, Franke, 2013 carried out with senior citizens in which the PIL questionnaire was used, it was observed that more elderly people presented significantly more meaning of life. This line is still in an embryonic stage with the development of the gerotranscendence construct (Tornstam, 2011), and there is a debate (ethics of care vs. ethics of needs) about which are the keys to be included in both diagnostic research as well as derived lines of intervention (Cabaco and Fernández, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Franke, 2013 carried out with senior citizens in which the PIL questionnaire was used, it was observed that more elderly people presented significantly more meaning of life. This line is still in an embryonic stage with the development of the gerotranscendence construct (Tornstam, 2011), and there is a debate (ethics of care vs. ethics of needs) about which are the keys to be included in both diagnostic research as well as derived lines of intervention (Cabaco and Fernández, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Following this line, greater satisfaction has been shown in terms of the health, good functional skills, a large number of social contacts, marital status, and the educational level of the senior population (Montenegro and Soler, 2013;Martín Aranda, 2018). Over recent years, other research has shown interest in studying life satisfaction in the intermediate and final stages of life, with results that do not always coincide (Guillén and Angulo, 2016;Jiménez et al, 2016;Cabaco and Fernández, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…La implementación de estas perspectivas apunta a que "[...] los cuidados de enfermería deben incluir la comprensión de las necesidades provocadas por el cambio de perspectiva vital [...]" (Wadensten & Carlsson, 2007a, p. 300). Se introduce el elemento de las necesidades como pivote del cuidado, en sintonía con Sánchez Cabaco & Fernández Mateos (2019). La enfermería es una disciplina que asienta sus bases en el cuidado del paciente desde la perspectiva del cuidado del cuerpo, pero ello no debe impedir que el cuidador debe asentar dicho cuidado de las personas mayores sobre la base de unas perspectivas que tengan como fundamento la persona mayor y sus necesidades.…”
Section: Gerotrascendencia Y Cuidados Sanitariosunclassified
“…However, the literature lacks a structured review of the existing evidence on gerotranscendence interventions and, thus, remains unclear on the characteristics of effective interventions, such as the way they are executed, the way gerotranscendence is addressed, and the associated outcomes. Systematizing these details can provide a greater understanding of whether and, if so, how gerotranscendence links to the benefits outlined in previous exploratory studies in practical terms and would add to existing evidence on interventions to support older adults' mental health, well-being, and life satisfaction (Sánchez Cabaco and Fernández Mateos, 2019;Raeesi Dehkordi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The relation between existential reflections and gerotranscendence ( van Rhyn et al, 2022 ), the multiple pathways to achieving it ( Tornstam, 2005 ), and older adults’ natural identification with the theory ( Heinz et al, 2017 ) suggest interventions can help develop and/or enhance gerotranscendence ( Sánchez Cabaco and Fernández Mateos, 2019 ). Such interventions may also improve older adults’ mental health, as higher levels of gerotranscendence has been associated with a greater degree of well-being, purpose in life, and life satisfaction and with lower levels of depression, anxiety, and fear of death ( Braam et al, 2006 , 2016 ; George & Dixon, 2018 ; Raeesi Dehkordi et al, 2020 ; Wang, 2011 ; Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%